Pengaruh Live Streaming, Diskon Tanggal Kembar, Gratis Ongkir, Dan Ulasan Produk Terhadap Minat Beli - Ganesha, Galland; Setiawan, Budi; Rosmawaty, Rosmawaty (Forum Kerjasama Pendidikan Tinggi, 2025)
This research analyzes the influence of live streaming, twin date discounts, free shipping, and product reviews on interest buy for students in Palembang City when shopping on Shopee. With the development of e-commerce, promotional strategies have become crucial in attracting consumers. This research also shows the relevance of e-commerce in supporting the achievement of the United Nations Sustainable Development Goals (UN SDGs), especially in accelerating economic growth (SDG 8). Data was collected through a survey of 96 respondents and analyzed using PLS-SEM. The research results show that live streaming and free shipping have no effect on buying interest. In contrast, twin date discounts and product reviews have a positive and significant influence. These findings provide insight for Shopee to optimize promotional strategies to increase competitiveness. Theoretically, this research contributes to digital marketing literature and supports the implementation of SDGs through more inclusive and sustainable e-commerce promotion innovation.